Fungal and oomycete pathogens and heavy metals: an inglorious couple in the environment - Joanna Gajewska; Jolanta Floryszak-Wieczorek; Ewa Sobieszczuk-Nowicka; Autar Mattoo; Magdalena Arasimowicz-Jelonek (IMA Fungus)
Abstract Heavy metal (HM) contamination of the environment is a major problem worldwide. The rate of global deposition of HMs in soil has dramatically increased over the past two centuries and there of facilitated their rapid accumulation also in living systems. Although the effects of HMs on plants, animals and humans have been extensively studied, yet little is known about their effects on the (patho)biology of the microorganisms belonging to a unique group of filamentous eukaryotic pathogens, i.e., fungi and oomycetes. Much of the literature concerning mainly model species has revealed that HM stress affects their hyphal growth, morphology, and sporulation. Toxicity at cellular level leads to disturbance of redox homeostasis manifested by the formation of nitro-oxidative intermediates and to the induction of antioxidant machinery. Despite such adverse effects, published data is indicative of the fact that fungal and oomycete pathogens have a relatively high tolerance to HMs in comparison to other groups of microbes such as bacteria. Likely, these pathogens may harbor a network of detoxification mechanisms that ensure their survival in a highly HM-polluted (micro)habitat. Such a network may include extracellular HMs immobilization, biosorption to cell wall, and/or their intracellular sequestration to proteins or other ligands. HMs may also induce a hormesis-like phenomenon allowing the pathogens to maintain or even increase fitness against chemical challenges. Different scenarios linking HMs stress and modification of the microorganisms pathogenicity are disscused in this review.